Phase-resolved MRI for measurement of pulmonary perfusion and ventilation defects in comparison with dynamic contrast-enhanced MRI and 129Xe MRI - Ouyang, Tao; Tang, Yichen; Zhang, Chen; Yang, Qi (BMJ open respiratory research, 2024)
IntroductionThis meta-analysis aims to evaluate the agreement and correlation between phase-resolved functional lung MRI (PREFUL MRI) and dynamic contrast-enhanced (DCE) MRI in evaluating perfusion defect percentage (QDP), as well as the agreement between PREFUL MRI and 129Xe MRI in assessing ventilation defect percentage (VDP).MethodA systematic search was conducted in the Medline, Embase and Cochrane Library databases to identify relevant studies comparing QDP and VDP measured by DCE MRI and 129Xe MRI compared with PREFUL MRI. Meta-analytical techniques were applied to calculate the pooled weighted bias, limits of agreement (LOA) and correlation coefficient. The publication bias was assessed using Egger’s regression test, while heterogeneity was assessed using Cochran’s Q test and Higgins I2 statistic.ResultsA total of 399 subjects from 10 studies were enrolled. The mean difference and LOA were −2.31% (−8.01% to 3.40%) for QDP and 0.34% (−4.94% to 5.62%) for VDP. The pooled correlations (95% CI) were 0.65 (0.55 to 0.73) for QDP and 0.72 (0.61 to 0.80) for VDP. Furthermore, both QDP and VDP showed a negative correlation with forced expiratory volume in 1 s (FEV1). The pooled correlation between QDP and FEV1 was −0.51 (−0.74 to −0.18), as well as between VDP and FEV1 was −0.60 (−0.73 to −0.44).ConclusionsPREFUL MRI is a promising imaging for the assessment of lung function, as it demonstrates satisfactory deviations and LOA when compared with DEC MRI and 129Xe MRI.PROSPERO registration numberCRD42023430847.